Pengaruh Disiplin Kerja Dan Kualitas Pelayanan Pegawai Kantor Desa Terhadap Kepuasan Masyarakat Desa Tenggulun Kecamatan Solokuro Kabupaten Lamongan - Muamar Kadhafi; Abdul Kodir Djaelani; Eka Farida (UNIVERSITAS ISLAM MALANG, 2022)
Abstract This study aims to observe the impact of labor discipline and service exceptional of village workplace personnel on network delight in Tenggulun Village, Solokuro District, Lamongan Regency. The population in this study was the entire community of Tenggulun Village, Solokuro District, Lamongan Regency, amounting to 2,348. The sample in this study used Slovin's theory with the number of samples obtained, namely 96 respondents. The research method in this study uses quantitative research with an Explanatory Research approach. Based on testing using simultaneous F-test evaluation, the results showed that there has been a extensive impact among the X variables (work discipline and service quality) simultaneously on the Y variable (community satisfaction) in Tenggulun Village, Solokuro District, Lamongan Regency, and the outcomes of the partial t-test. The results confirmed that the paintings area variable had a effective and great impact on network pride in Tenggulun Village, Solokuro District, Lamongan Regency and provider nice had a nice and significant effect on community pleasure in Tenggulun Village, Solokuro District, Lamongan Regency. Keywords : Work Discipline, Service Quality, Community Satisfaction